The ribosomal A-site finger is crucial for binding and activation of the stringent factor RelA. Issue 4 (30th January 2018) - Kudrin, Pavel; Dzhygyr, Ievgen; Ishiguro, Kensuke; Beljantseva, Jelena; Maksimova, Elena; Oliveira, Sofia Raquel Alves; Varik, Vallo; Payoe, Roshani; Konevega, Andrey L; Tenson, Tanel; Suzuki, Tsutomu; Hauryliuk, Vasili
Abstract: During amino acid starvation the Escherichia coli stringent response factor RelA recognizes deacylated tRNA in the ribosomal A-site. This interaction activates RelA-mediated synthesis of alarmone nucleotides pppGpp and ppGpp, collectively referred to as (p)ppGpp. These two alarmones are synthesized by addition of a pyrophosphate moiety to the 3′ position of the abundant cellular nucleotide GTP and less abundant nucleotide GDP, respectively. Using untagged native RelA we show that allosteric activation of RelA by pppGpp increases the efficiency of GDP conversion to achieve the maximum rate of (p)ppGpp production. Using a panel of ribosomal RNA mutants, we show that the A-site finger structural element of 23S rRNA helix 38 is crucial for RelA binding to the ribosome and consequent activation, and deletion of the element severely compromises (p)ppGpp accumulation in E. coli upon amino acid starvation. Through binding assays and enzymology, we show that E. coli RelA does not form a stable complex with, and is not activated by, deacylated tRNA off the ribosome. This indicates that in the cell, RelA first binds the empty A-site and then recruits tRNA rather than first binding tRNA and then binding the ribosome.